ACT jako forma wsparcia młodzieży w budowaniu zdrowych nawyków żywieniowych - Klon, Weronika; Waszyńska, Katarzyna (Rocznik Pedagogiczny, 2020)
The aim of the article is to describe the process of the change of eating habits in adolescence in ref- erence to the psychological flexibility theory which has its origins in Acceptance and Commitment Therapy (ACT). The processes of mental and physical development of teenagers are also included. The article contains descriptions of the mechanisms of formation and change of the eating habits in adolescence. This content was referred to all elements of psychological flexibility: mindfulness, values, acceptation, cognitive defusion, self as context and committed action.